Analisis dan Perancangan Sistem Informasi Administrasi Balai Pelatihan Kesehatan - Pahrulloh Pahrulloh; M. Haviz Irfani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2016)
The rapid development of computer and information technology (CIT) has been the triggers for various companies, including BAPELKES (Health training center) of South Sumatra province, to apply the CIT based on the web and desktop system. However, there are some problems regarding the CIT implementation process such as long distance issue, the accuracy of training result and the data shortage obtained from periodic training report. Therefore, BAPELKES needs an information system to increase global competition chances and to improve the company existence value. The RUP (Rational Unified Process) by iteration method is used as CIT methodology. Then, the implementation of program design uses PHP (Personal Home Page) language version 6.0, whilst the DBMS (Database Management System) application uses MySQL. The web-based administration information system is expected providing more facilities and minimizing errors occurred in administration and stakeholders levels involved in the training activities.